Answer:
B
Step-by-step explanation:
Let us assume the number of children attending the movie = x
Let us also assume the number of adults attending the movie = y
Cost of admission for a children in the movie = $8
Cost of admission of an adult in the movie = $12
Number of people going to the movie on a certain day = 3200
Total amount collected from the movie theater = $33040
Then
x + y = 3200
And
8x + 12y = 33040
2x + 3y = 8260
Let us first take the equation
x + y = 3200
x = 3200 - y
Now we will put the value of x in the equation
2x + 3y = 8260
2(3200 - y) + 3y = 8260
6400 - 2y + 3y = 8260
y = 8260 - 6400
= 1860
Now we will put the value of y from the above deduction in the equation
x + y = 3200
x + 1860 = 3200
x = 3200 - 1860
= 1340
So the number of children going to the movie theater is 1340 and the number of adults going to the movie theater is 1860.
Answer:
x = -2
Step-by-step explanation:
For this problem, we must simply solve for x. To do this, we will need equation operations, and the use of the distributive property.
Let's work this line by line until we have the value for x:
3{-x + (2x + 1)} = x - 1
3*-x + 3*(2x + 1) = x - 1
-3x + 6x + 3 = x - 1
3x + 3 = x - 1
2x = -4
x = -2
Now we can check our answer for x by plugging back into the original equation and see if the left hand side is equal to the right hand side:
3{-x + (2x + 1)} = x - 1
3{-(-2) + (2(-2) + 1)} ?= (-2) - 1
3{2 + (-4 + 1)} ?= -3
3{2 + (-3)} ?= -3
3{-1} ?= -3
-3 == -3
Thus, we have found the solution for x to be equivalent to negative 2.
Cheers.